Significantly improved high-temperature performance of polymer dielectric via building nanosheets and confined space. (1st September 2020) - Nie, Run-Pan; Lei, Jun; Jia, Li-Chuan; Chen, Chao; Xu, Ling; Li, Yue; Huang, Hua-Dong; Yu, Feng-Mei; Li, Zhong-Ming
Abstract: Polymer dielectrics generally cannot meet the requirements of high-temperature capability and high dielectric properties due to the exponential increasement of dielectric loss with increasing temperature. Herein, a scalable strategy to significantly enhance the high-temperature dielectric performance of polymer dielectrics was reported. Polyvinylidene fluoride (PVDF) nanosheets with large width/thickness ratio were successfully constructed in the polycarbonate (PC) film utilizing the "extrusion-stretching-compression" technology. This structure endowed PC/PVDF blend films with superior dielectric properties. The dielectric constant ( ε r ' ) of the blend films increased from 4.4 (common PC/PVDF blend films) to 5.3, and the dielectric loss (tan δ ) decreased from 8.2 × 10 −3 to 6.1 × 10 −3 . More importantly, the blend films with highly ordered nanosheets exhibited great restriction effect on the ion conduction owing to the synergistic effect of the phase morphology and chain mobility. Through combining the highly ordered PVDF nanosheets and confined space provided by the PC matrix, a "cage" for impurity ions has been successfully created, rendering the large suppression of ionic conduction loss at elevated temperatures (up to 150 °C). The excellent comprehensive properties demonstrate a facile route to fabricate high-temperature and high dielectric performance polymer dielectrics required in electric vehicles, aerospace power electronics, etc.